Reimagining the Way of the Cross: A Contemporary Multilayered Visualization Based on The Passion - Brian Alvin Hananto; Sharon Hardjono; Winoto Usman (Universitas Pelita Harapan, 2025)
The Way of the Cross is a central devotional practice in Catholicism, yet its traditional visual representations often fail to resonate with younger generations. This study explores how contemporary art, specifically a multilayered visual approach, can revitalize engagement with the Via Dolorosa. Based on a devotional book, “The Passion” by James Traynor, which presents each station from a character’s perspective, this design project transforms textual testimonies into layered visual interpretations. The study applies Bandura’s Social Cognitive Theory to analyze character motivations and structure visual storytelling. The design methodology follows an exploratory model consisting of pre-design research, conceptual development, and final production. The design offers a new way to experience the Way of the Cross, encouraging personal reflection through layered visuals and character-based storytelling.